The Interaction of Production, Distribution and Rule-Making Systems in Industrial Relations - Lee, Hyo (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
This paper proposes to see industrial relations as a synthesis of production, distribution, and rule-making Systems (PDR Systems) rather than to regard these three Systems as independent forces. This PDR System theory focuses on the actors' strategic choices for the PDR Systems, that is, subsystems of industrial relations System, and their interaction mechanisms. The contents and interactions of the PDR Systems determine the performance levels of the organization, i.e., productivity, flexibility, innovation, fairness, and satisfaction. This model can be used to analyze nonunion workplaces as well as unionized settings by embracing collective bargaining as a subsystem of the rule-making System. The general framework of the model is illustrated by using data from a Korean automobile company, which is particularly well suited for this purpose since it reflects different combinations of different PDR practices over its history. This model demonstrates that the best practice of future industrial relations will be established by the PDR Systems in which the creative humanware is maximized and actors spontaneously cooperate.